Correction of factor XI deficiency by liver transplantation. Issue 8 (December 2015) - Gupta, Eva; Finn, Laura; Johns, Gretchen; Pruthi, Rajiv K.; Roy, Vivek
Abstract : Orthotopic liver transplantation for other diseases typically results in a coincidental cure for hemophilia A and B; however, long-term outcomes of liver transplant in hemophilia C are not very well described. Herein, the authors report a patient of severe congenital factor XI (FXI) deficiency who received an orthotopic liver transplant. The authors discuss the perioperative management and long-term outcomes. The normalization of his FXI levels confirms that the liver is the most clinically relevant site of synthesis of FXI.